2010
DOI: 10.1136/ip.2010.029546
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the effect of compensation on recovery from severe motor vehicle crash injuries: a qualitative study

Abstract: The injury recovery experience was difficult for all subjects, but it was particularly stressful for those claiming compensation. Based on this study, the claims process, particularly medico-legal examinations, and other factors that could impact on injury recovery, are targets for further research, possible policy review, or legislative change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 25 publications
4
62
0
1
Order By: Relevance
“…In reality this means that with the exception of some claimants (those that can establish severe hardship), many claimants do not have access to their compensation entitlements for extended periods of time [18]. This is a consistent finding in compensation research where claimants have reported issues of 'financial hardship' and difficult experiences in returning to work post injury [16]; and another reporting that stress is associated with understanding the requirements of the claiming process and the time taken to deal with their claims [32]. Given the reported complexities and numerous stressors, it is plausible that it is these stressors, specifically extended exposure to them that contributes to the increasing numbers with lawyer involvement at 12 months post injury.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In reality this means that with the exception of some claimants (those that can establish severe hardship), many claimants do not have access to their compensation entitlements for extended periods of time [18]. This is a consistent finding in compensation research where claimants have reported issues of 'financial hardship' and difficult experiences in returning to work post injury [16]; and another reporting that stress is associated with understanding the requirements of the claiming process and the time taken to deal with their claims [32]. Given the reported complexities and numerous stressors, it is plausible that it is these stressors, specifically extended exposure to them that contributes to the increasing numbers with lawyer involvement at 12 months post injury.…”
Section: Discussionmentioning
confidence: 53%
“…Scheme participants report that they require 'legal representation to negotiate with insurers and steer them through the claims process despite often disliking the involvement of a lawyer' [16]. Other stress inducing factors occurring within the compensation system such as the frequency of medico-legal assessments and insufficient claims information have been linked to increased legal representation [17].…”
Section: Introductionmentioning
confidence: 99%
“…For most, working is a financial necessity so recovery [3] and RTW from an unexpected injury are important to workers and their families if only for financial reasons. Murgatroyd et al (2010) considered the effect of compensation on recovery following severe motor vehicle crash injuries and suggested that recovery was particularly stressful for those claiming compensation [9]. In the current study, around half of the participants were in receipt of injury compensation.…”
Section: Discussionmentioning
confidence: 81%
“…Qualitative research has explored recovery from the perspective of the injured person following physical trauma, lower back pain, hand injuries, and upper limb musculoskeletal disorders [9][10][11][12]. Various themes have emerged from these studies including the "importance of the injury event" and "moving on from the trauma" as well as the role of family and work support.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have looked at the impact of the claims process, interactions between injured workers, health care providers and insurers [2123], and financial and employment considerations [24]. Results showed having a compensation claim had largely negative influence on injury recovery.…”
Section: Introductionmentioning
confidence: 99%